Application of The Completely Random Design Statistics Method For Analysis of Different Filter Types In Fresh Water Fish Pool Water Recirculation System - Heru Kartika Candra; Syamsudin Noor; Muhammad Bahit; Rinova Firman Cahyani; Dwi Mulyani (Publisher Cv. Inara, 2023)
In meeting their daily water needs (bathing and washing), the majority of the people of South Kalimantan (South Kalimantan) have been using river water and peat well water, as is the case for fresh water fisheries. However, the water used is cloudy and smells because it is water that is polluted by household waste, and of course it shows the quality of the water that is still being debated for the process of fish cultivation. In the process of cultivating freshwater fish, the standard mechanism is still used, namely by making tarpaulin ponds for fish ponds and river water as a medium for fish cultivation and the process of providing feed. In the process there are several things about water quality and conditions, and several other issues, namely about water circulation, temperature, humidity, pH and oxygen regulation of fish pond water. Fish excrete waste from leftover feed and metabolism which contain lots of ammonia (Effendi, 2003). Fish excrete 80-90% of ammonia through osmoregulation processes, feces and from urine. To produce quality pond water as a medium for fish cultivation, it is necessary to have a proper and good water filter. This study aims to obtain the best filter substrate in increasing the growth and survival of freshwater fish fry reared using polluted river water in a tarpaulin pond with a recirculation system. The filter method used in this study was an experimental method using one factor Completely Randomized Design (CRD) with four treatment levels and three replications. The treatments applied were P0 = Zeolite, Charcoal, Japmate, Bio Foam, P1 = Bamboo, Charcoal, Japmate, Bio Foam, P2 = Bioball, Charcoal, Japmate, Bio Foam and P3 = Bioring, Charcoal, Japmate, Bio Foam. The resulting data were analyzed for analysis of variance (ANOVA), then continued using the BNT test with 95% and 99% confidence intervals. From the results of the study, the measurement results obtained were for the specific growth rate test (SGR) of 1.15%, the survival test (SR) of 86.66% and the feed conversion ratio test (FCR) of 3.10%. While the supporting parameters are water quality, namely the results of water quality, namely, temperature 28.1 – 30.3 0C, pH 7.4 – 8.1, DO 5.24 6.53 mg/L, NH3 0.06 – 0.40 mg/L, NO2 0.056 – 0.90 mg/L and NO3- 0.28 – 0.190 mg/L. In addition to producing filter products that can support SGR, SR and FCR in freshwater fish, it is hoped that this research will also produce scientific paper outputs that will be published in International Conferences/International Journals and become part of the Study Program's Coursebook for the Accounting Department. Computerized Poliban Accounting and can be applied in the community through the Community Service program